Can Shallot Compress Reduce Fever in Children? A Supportive Nursing Intervention - Furtuna, Intan Syah Bintang; Juliningrum, Peni Perdani; Sulistyorini, Lantin; Inganah (Al-Hijrah Indonesia, 2025)
Background: Dengue Hemorrhagic Fever (DHF), an infectious disease transmitted by Aedes aegypti mosquitoes, frequently causes epidemics and can lead to fatal outcomes. A common clinical manifestation of DHF is hyperthermia (high fever), which requires prompt management. While pharmacological interventions like paracetamol or ibuprofen are standard, non-pharmacological therapies such as shallot (onion) compresses may offer supportive benefits. Objective: This study aimed to evaluate the effectiveness of shallot compress therapy in reducing fever in pediatric DHF patients. Methods: A case study was conducted in the Aster Room of Dr. Soebandi Hospital, involving children diagnosed with DHF and hyperthermia. Shallot compresses were applied as a non-pharmacological intervention, and temperature changes were monitored. Results: The study demonstrated a significant reduction in body temperature following the application of shallot compresses, indicating its efficacy as a supportive therapy for fever management in DHF. Conclusion: Shallot compress therapy is an effective non-pharmacological intervention to alleviate hyperthermia in pediatric DHF patients. Further research with larger samples is recommended to validate these findings.